Ignatius of Antioch and the Arian controversy - Gilliam, Paul R. (Vigiliae Christianae, Supplements, 2017)
In Ignatius of Antioch and the Arian Controversy , Paul R. Gilliam III contends that the legacy of the second-century martyr Ignatius of Antioch was one battleground upon which Nicene and Non-Nicene personalities fought for their understanding of the relationship of the Son to the Father. It is well-know that Ignatius' views continued to live on into the fourth century via the long recension of his letters. Gilliam, however, shows that there was much more to Ignatius' fourth-century presence than the Ignatian long recension.